Quantificação em ácidos graxos, antioxidantes e desenvolvimento de metodologia para extração lipídica, em tecido muscular de peixes - Montanher, Paula Fernandes (2014)
The aim of this study was to investigate the antioxidant capacity of hydrophilic and lipophilic extracts from fish muscle tissue, applying ORAC methodology Oxygen Radical Absorbance Capacity). A study of fatty acid composition and the development of a new method for total lipids extraction were also performed. This study was divided into four chapters, in which Chapter I is the review, Chapter II deals with the information related to the study of fatty acids and antioxidants incorporation in Nile tilapia (Oreochromis niloticus) fed with diet enriched in chia (Salvia hispanica) oil and avocado (Persea americana) peel extract. That study found an increase in total omega-3 fatty acids and antioxidant capacity of lipophilic fraction (L-ORAC(FL)) in treatments where there was the inclusion of chia oil after 45 days of feeding. In Chapter III a survey of antioxidant capacity and fatty acid composition of six fish species common in the southern brazilian coast was conducted. All species showed significant amounts of fatty acids eicosapentaenoic (EPA, 20: 5n-3) and docosahexaenoic (DHA, 22: 6n-3), a Person's correlation coefficient (r) of 0.72 was obtained between poly-unsaturated fatty acids and lipophilic antioxidant capacity. Chapter IV presents the proposed methodology for total lipids (TL) extraction from fish muscle tissue, using lower toxicity solvents, as an alternative methodology for Bligh & Dyer (1959). There was no statistical difference (p <0.05) in the levels of TL obtained by the proposed method and the Bligh & Dyer